A produção partilhada do conhecimento na vivência com a comunidade indígena Bororo: princípios para uma ciência cidadã - Ribeiro, Geisa Müller de Campos (2023)
The research aims to raise, together with the Bororo indigenous peoples and researchers who carry out research/teaching in the Meruri village, the principles present in the dynamics of the shared construction of scientific knowledge. It is intended to identify the dynamics established for the shared production of knowledge; punctuate institutional and territorial tensions and ruptures and what they reveal in the scope of production, legitimation/verification and sharing of the produced knowledge; discuss the communication that is set or that is demanded in the relationship with this group; reflect on the concept and foundations that Citizen Science demands. From a methodological point of view, the research is influenced by decolonial methodologies where the community does not act as an object, but as a subject of knowledge production sharing. It is a context in which there is no single model and normative uses of types of research, as it is an instrument within popular action that takes place in another dimension of time and space, and uses the shared production of knowledge as its foundations. This indigenous group has been demanding cognitive justice and epistemic diversity in science, breaking with scientific endeavors that commit epistemicide. They fight for autonomy to fully exercise their capacities to use, share and create knowledge. In the research, we sought to develop the dialogues in 3 ways: 1. The reception of the community. 2. Sharing of knowledge in loco based on the objectives. 3. Data evaluation: return of knowledge. These steps were the foundations of the research for 14 months (2021/2023). Long individual and group conversations were held. The aim was to overcome some of the limitations of the traditional survey format and let the sharing group tell its own story. That is, who was spoken, assumes the speech in the process. These long conversations are taken as testimony, a broad narrative that considers a person as the bearer of the dimension of their collectivity. Developing the research in a way ofsharing provided the creation of the Bororo indigenous expression “Panure Paeruduwa Maku Puibagi” which is the living/experience itself; communication base between researchers and the Boe and which hasits own sharing economy guided by the idea of exchange. The reflectionsshowed the need to form a language capable of giving meaning to certain abstractions that are part of the local context and that citizen science must pay attention to this activation. In this, there is a withdrawal from the claim of scientific language as unique, universal, towards the understanding that there are “languages” and particular logics, the result of the local context. The concepts presented give us clues to reflect on the construction of the basis of a Citizen Science that breaks with hegemonic universalism and this is a political and emancipatory act; it produces situated knowledge, which comes from a reconstruction of objectivity; brings to the centrality the tension of talking about the object, to talk and produce knowledge With; it does not have ready-made methods, but they are built on the go, together and consistent with situated knowledge; suspends linear time to establish a coexistence with local time; it is intercultural because it allows the coexistence of logics of ethnicity and citizenship in the same social and territorial space; it tensions the locus of knowledge production, but at the same time seeks to create objective conditions for these groups to appropriate the University; and it is not a proprietary science, but one that follows collective criteria and norms. These questions indicate that the citizenship of science finds its maximum expression in the relationship of otherness that requires overcoming the limited and ethnocentric notion of the concept of citizenship. It manifests itself, then, in the recognition of oneself and the other so that there is cognitive justice and the full exercise of citizenship in the scientific field, which for the Boe is to have the autonomy to speak about oneself without the tutelage of anyone. Being a citizen is to be a subject and not an object of research, it is to produce and have your data recognized in the debate and in society's major development strategies.